Surface and interface modification method of Prussian blue positive electrode material

The modified Prussian blue positive electrode material was prepared by co-precipitation method, which solved the problems of Prussian blue in sodium ion batteries, and achieved high specific capacity, excellent cycle stability and rate performance, with broad industrial application prospects.

CN119569083APending Publication Date: 2025-03-07ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411776311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

As the cathode material of sodium ion batteries, Prussian blue has low capacitance, capacity attenuation, structural damage and low conductivity limits the battery's energy density, cycle life and high power output performance.

Method used

Modified Prussian blue positive electrode material was prepared by co-precipitation method. The modified Prussian blue powder was prepared by co-precipitation of sodium citrate, FeSO4·7H2O and Na4Fe(CN)6·10H2O in a specific proportion of solution, and the modified metal titanium ion solution was added. The modified Prussian blue powder was prepared by mixing it with conductive carbon black and polyvinylidene fluoride.

Benefits of technology

It improves the specific capacity, cycle stability and rate performance of the modified Prussian blue battery, extends the cycle life of the battery, reduces the cost of the battery, and has broad industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569083A_ABST
    Figure CN119569083A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface and interface modification of a battery positive electrode material, and discloses a surface and interface modification method of a Prussian blue positive electrode material, which comprises the following steps: mixing sodium citrate and FeSO4. 7H2O in deionized water to prepare a 100mL solution marked as a solution a; the mass ratio of the sodium citrate to the FeSO4. 7H2O is (6-8): (1-3); dissolving sodium citrate and Na4Fe (CN) 6. 10H2O in deionized water to form a 100mL solution, and marking the 100mL solution as a solution b; the mass ratio of the sodium citrate to the Na4Fe (CN) 6. 10H2O is (6-8): (1-2.5). The material is prepared by adopting a coprecipitation method, modification of the surface interface of the Prussian blue positive electrode material is realized by directly utilizing metal titanium ions, and the method is simple and efficient in experimental operation and mild in condition, and has a relatively wide application prospect in actual industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of interface modified battery positive electrode materials, in particular to a surface interface modification method of a Prussian blue positive electrode material. Background Art

[0002] With the rapid development and popularization of renewable energy, energy storage batteries have emerged as a key technology. Renewable energy sources such as solar and wind energy are intermittent and volatile, making it impossible for energy production to stably meet demand. The emergence of energy storage batteries fills the gap between energy production and demand, providing flexibility and reliability for the energy system. Energy storage batteries can store excess renewable energy, so that electricity can be released when energy demand peaks, balancing the load of the power grid and improving energy efficiency. This ability to store and release energy on demand helps reduce dependence on traditional fossil fuels and promote the widespread application of clean energy. At present, the main energy storage batteries are lithium-ion batteries and sodium-ion batteries. Lithium-ion batteries are in urgent need of alternative products due to resource scarcity and high cost. Safe sodium-ion batteries have attracted widespread attention. However, one of the key issues of sodium ions is the lack of positive electrode materials with high rate performance and long cycle life. Prussian blue is an excellent sodium ion host because it has an open 3D internal framework that is conducive to the reversible transmission of sodium ions. However, Prussian blue, as a positive electrode material for sodium-ion batteries, has a low capacity that limits the energy density of the battery and is not conducive to improving the overall performance of the battery. In addition, Prussian blue is prone to capacity attenuation and structural damage during long-term charge and discharge cycles, which limits the cycle life of the battery. At the same time, Prussian blue has low conductivity, which may lead to performance degradation at high power output. These factors, coupled with high costs, make its commercialization and large-scale application face certain challenges, and further research and improvement are needed to improve the comprehensive performance and economic feasibility of sodium-ion batteries. Summary of the invention

[0003] In order to solve the technical problems raised in the background technology, the present invention provides a method for preparing a modified Prussian blue positive electrode material.

[0004] The present invention is implemented by the following technical solution: A method for preparing a modified Prussian blue positive electrode material comprises the following steps:

[0005] Sodium citrate and FeSO4·7H2O were mixed in deionized water to prepare a 100 mL solution, which was labeled as solution a; the mass ratio of sodium citrate to FeSO4·7H2O was 6-8:1-3;

[0006] Then, sodium citrate and Na4Fe(CN)6·10H2O were dissolved in deionized water to form 100 mL of a solution, which was marked as solution b; the mass ratio of sodium citrate to Na4Fe(CN)6·10H2O was 6-8:1-2.5.

[0007] Then, solution a was dropped into solution b while adding the modified metal ion solution, stirred at 500 rpm for 3 h, aged for 3 h, and then the precipitate was collected by suction filtration and washed several times with deionized water and ethanol;

[0008] Finally, the obtained powder was dried in a vacuum oven at 80-100° C. for 12 h to obtain modified Prussian blue powder.

[0009] Preferably, the solution a is dripped into the solution b at a constant speed of 4 mL / min. -1 .

[0010] Preferably, the mass ratio of sodium citrate, FeSO4·7H2O and Na4Fe(CN)6·10H2O is 7.5:1.67:1.94, and the concentration of the titanium ion solution is 0.5-4.0 mol.L -1 .

[0011] The present invention provides a method for preparing a positive electrode sheet of a battery, comprising the following steps:

[0012] Weigh the modified Prussian blue solid powder, conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1; first mix and grind the modified Prussian blue solid powder and the conductive carbon black evenly, then add polyvinylidene fluoride and an appropriate amount of solvent N-methylpyrrolidone, grind them evenly and then coat them evenly on aluminum foil, then put them into a vacuum drying oven at 80°C and dry them for 12 hours to obtain the required battery positive electrode sheet.

[0013] A positive electrode plate of a battery is prepared by adopting the above method.

[0014] The present invention also proposes a battery preparation method, comprising the following steps: using the above-mentioned electrode sheet as the positive electrode and the sodium sheet as the negative electrode to assemble a button battery, the battery assembly process is the positive electrode shell, the electrode sheet, the electrolyte, the diaphragm, the sodium sheet, the gasket, the spring sheet, the negative electrode shell, and then using a button battery sealing machine to press the battery to ensure good contact between the positive and negative electrodes.

[0015] The battery was used for cyclic voltammetry test and constant current charge and discharge test:

[0016] Button cell battery cycle stability test

[0017] Place the prepared button cell in a constant temperature box, set up the program, and test its cyclic charge and discharge performance at a certain rate.

[0018] Rate performance test of button cell:

[0019] Place the prepared button cell in a constant temperature box, set up the program, and test its cyclic charge and discharge performance at different rates.

[0020] Button cell electrochemical cyclic voltammetry test:

[0021] By measuring the cyclic voltammetry curve of the button battery electrode, the number and shape of the CV curve peaks in the material are analyzed, the adsorption / desorption process is studied, and the diffusion coefficient of the reactants is estimated to infer the reaction mechanism.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts a co-precipitation method to prepare the material, and directly synthesizes a novel Prussian blue solid powder in one step. The experimental operation is simple and efficient, the conditions are mild, and it has a broad application prospect in actual industrial applications.

[0024] 2. Compared with pure Prussian blue, the battery prepared by the modified Prussian blue prepared by the present invention exhibits high specific capacity, excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The X-ray diffraction patterns of the modified Prussian blue and pure Prussian blue solid powder prepared by the present invention are shown.

[0026] Figure 2 The figures are scanning electron microscope pictures of the modified Prussian blue and pure Prussian blue solid powder prepared by the present invention.

[0027] Figure 3 These are transmission and high-resolution images of the modified Prussian blue and pure Prussian blue solid powders prepared by the present invention.

[0028] Figure 4 Infrared spectra of the modified Prussian blue and pure Prussian blue solid powders prepared by the present invention.

[0029] Figure 5 The figure is a charge and discharge curve diagram of the modified Prussian blue and pure Prussian blue solid powder prepared by the present invention at a rate of 0.2C.

[0030] Figure 6 It is a specific capacity diagram of the modified Prussian blue and pure Prussian blue solid powder prepared by the present invention at different magnifications.

[0031] Figure 7a It is a cycle diagram of the modified Prussian blue and pure Prussian blue solid powder prepared by the present invention at a 2C rate.

[0032] Figure 7b It is a cycle diagram of the modified Prussian blue and pure Prussian blue solid powder prepared by the present invention at a 5C rate. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0034] Example 1: A method for preparing a modified Prussian blue positive electrode material, comprising the following steps: Synthesis of modified Prussian blue solid powder: The sample was synthesized at room temperature by precipitation method. 7.5 g sodium citrate and 1.67 g FeSO4·7H2O were mixed in deionized water to prepare a 100 mL solution, which was labeled as solution a. 7.5 g sodium citrate and 1.94 g Na4Fe(CN)6·10H2O were dissolved in deionized water to form a 100 mL solution, which was labeled as solution b. Then, solution a was dripped into solution b (4 mL min -1 ) and add 0.9 mol.L -1 The titanium ion solution was stirred at 500 rpm for 3 h, aged for 3 h, and then the precipitate was collected by suction filtration, washed with deionized water and ethanol several times. Finally, the obtained powder was dried in a vacuum oven at 80-100 ° C for 12 h.

[0035] Example 2: A method for preparing a positive electrode of a battery: 70 mg of the modified Prussian blue solid powder and 20 mg of carbon black prepared in Example 1 were placed in a mortar and ground thoroughly, 333.3 mg of 3% (mass fraction) polyvinylidene fluoride (solvent is N-methylpyrrolidone) was added, and the mixture was ground thoroughly again to obtain a uniform black slurry, which was then coated on an aluminum foil. The mixture was placed in a vacuum drying oven and dried at 80°C for 12 hours to remove the solvent, and the dried electrode was punched into a small disc with a diameter of 14 mm using a punching machine.

[0036] Example 3. Button battery assembly:

[0037] The positive electrode sheet obtained in the above Example 2 was weighed, and button cells were assembled in an ultra-clean argon glove box, and the sodium sheet was assembled into a button cell as the negative electrode. The battery assembly process is the positive electrode shell, the electrode sheet, the electrolyte, the diaphragm, the sodium sheet, the gasket, the spring sheet, the negative electrode shell, and the electrode sheet coated with the material facing up; the electrolyte used is sodium perchlorate, and the amount is 150 microliters; the diaphragm is a battery-grade diaphragm; the diameter of the sodium sheet is 14mm, and the other components are directly purchased and used. Then the battery is pressed tightly using a button battery sealing machine to ensure good contact between the positive and negative electrodes. The battery is used for cycle, rate and cyclic voltammetry tests.

[0038] Battery performance test:

[0039] 1. Button cell cycle stability test: Place the assembled button cell in a 25℃ constant temperature box, set the program, theoretical specific capacity is 170mgh / g, voltage range is 2.0-4.0V, rate is set to 2C and 5C respectively, and the number of charge and discharge is 200 times. Test its performance of cycle charge and discharge at different rates.

[0040] 2. Rate performance test of button battery: Place the prepared button battery in a 25℃ constant temperature box, set the program, the theoretical specific capacity is 170mgh / g, the voltage range is 2.0-4.0V, the rate is 0.5C, 1C, 2C, 5C, 7C, 10C, 20C, increase step by step, and finally return to 0.5C. Cycle charge and discharge 10 times at each rate to test its performance of cyclic charge and discharge at different rates.

[0041] Result analysis:

[0042] As attached Figure 1 As shown, the modified Prussian blue solid powder was subjected to phase analysis using an X-ray diffraction pattern, and the obtained diffraction peaks corresponded one to one with the peaks of the Prussian blue standard card (PDF#52-1907), indicating that there was only a uniform Prussian blue phase without other impurity phases.

[0043] As attached Figure 2 As shown in the scanning electron microscope image, the synthesized modified Prussian blue material has a uniform morphology and uniform size, corresponding to the size of hundreds of nanometers. Compared with the pure Prussian blue sample, it has a more complete morphology and a larger surface area.

[0044] According to the HRTEM images (attached Figure 3 ) It can be seen that the corresponding crystal plane of the modified Prussian blue material is (200), which also proves the successful preparation of the material.

[0045] As attached Figure 4 The infrared spectrum curve shows that the intensity of the crystal water peak of the modified Prussian blue material is lower than that of the pure Prussian blue. When the crystal water content is reduced, it can provide a wider and smoother diffusion path for sodium ions, so that sodium ions can be embedded and extracted more quickly in the positive electrode material, speeding up the charge and discharge speed of the battery and improving the battery's rate performance.

[0046] As attached Figure 5As shown in the figure, the first charge and discharge curve at 0.2C. It can be seen from the figure that the material exhibits a typical charge and discharge platform curve unique to Prussian blue sodium ion batteries, showing the redox peaks of divalent iron ions to trivalent iron ions unique to Prussian blue at 2.8-3.1V and 3.8V. The initial discharge capacity of the modified Prussian blue sodium ion battery can reach 120.62mAh / g, while the initial discharge capacity of the sodium ion battery prepared with pure Prussian blue positive electrode material is only 106.64mAh / g.

[0047] As attached Figure 6 As shown, at different continuous rates, from 0.5C to 20C, the specific capacity and capacity retention ability of the modified Prussian blue positive electrode material are much higher than those of the pure Prussian blue material.

[0048] As attached Figure 7a As shown in the figure, the performance of the modified Prussian blue battery and the pure Prussian blue battery after 100 cycles was tested at a 2C rate. The test shows that the reversible discharge capacity of the modified Prussian blue sodium ion battery dropped from the initial 105.09 mAh / g to 102.64 mAh / g, and the capacity retention rate was 97.66%, showing excellent cycle stability compared with pure Prussian blue. As shown in the attached figure Figure 7b As shown in the figure, the cycle performance test was carried out at a rate of 5C. After 200 cycles, the reversible discharge capacity of the modified Prussian blue sodium ion battery dropped from the initial 106.02 mAh / g to 99.76 mAh / g, and the capacity retention rate was 94.09%, which also showed excellent cycle stability compared with pure Prussian blue.

[0049] The above content is an exemplary description of the present invention. It should be emphasized that as long as it does not deviate from the core essence of the present invention, even if it is just a simple change in form, a modification of details, or an equivalent replacement form that can be achieved by those skilled in the art without carrying out creative work, it should be included in the protection scope of the present invention.

[0050] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for modifying the surface interface of a Prussian blue cathode material, characterized in that: The method comprises the following steps: mixing sodium citrate and FeSO4·7H2O in deionized water to prepare a 100 mL solution, which is marked as solution a; the mass ratio of sodium citrate to FeSO4·7H2O is 6-8:1-3; Then, sodium citrate and Na4Fe(CN)6·10H2O were dissolved in deionized water to form a 100 mL solution, which was labeled as solution b; the mass ratio of sodium citrate to Na4Fe(CN)6·10H2O was 6-8:1-2.

5. Then, solution a was dropped into solution b and the modified metal titanium ion solution was added at the same time, stirred at 500 rpm for 3 h, aged for 3 h, and then the precipitate was collected by suction filtration and washed several times with deionized water and ethanol; Finally, the obtained powder was dried in a vacuum oven at 80-100° C. for 12 h to obtain modified Prussian blue powder.

2. The surface interface modification method of a Prussian blue positive electrode material according to claim 1, characterized in that: The solution a was dripped into the solution b at a constant speed of 4 mL / min. -1 .

3. The surface interface modification method of a Prussian blue cathode material according to claim 1, characterized in that: The mass ratio of sodium citrate, FeSO4·7H2O and Na4Fe(CN)6·10H2O is 7.5:1.67:1.94, and the concentration of the metal titanium ion solution is 0.5-4.0 mol.L -1 .

4. A method for preparing a positive electrode sheet of a battery, characterized in that: The steps include: Weigh the modified Prussian blue solid powder, conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1; first mix and grind the modified Prussian blue solid powder and the conductive carbon black evenly, then add polyvinylidene fluoride and an appropriate amount of solvent N-methylpyrrolidone, grind them evenly and then coat them evenly on aluminum foil, then put them into a vacuum drying oven at 80°C and dry them for 12 hours to obtain the required battery positive electrode sheet.

5. A positive electrode plate for a battery, characterized in that: The method according to claim 4 is adopted to prepare the present invention.

6. A method for preparing a battery, characterized in that: The method comprises the following steps: using the electrode sheet as claimed in claim 5 as the positive electrode and the sodium sheet as the negative electrode to assemble a button battery, wherein the battery assembly process is the positive electrode shell, the electrode sheet, the electrolyte, the diaphragm, the sodium sheet, the gasket, the spring sheet, the negative electrode shell, and then using a button battery sealing machine to press the battery tightly to ensure good contact between the positive and negative electrodes.